(untitled) (Sustainability in Debate, 2023)
The municipality of Petrópolis/RJ/Brazil is prone to extreme rainfall events that cause damage and direct and indirect economic losses. In order to verify the increase or not of these events, this study evaluates the temporal pattern of rainfall in the municipality (1976-2022), identifying whether the event that occurred in 2022 can be considered an extreme event, as well as the relationship between rainfall and impact intensity, in terms of damage and losses triggered. The accumulated rainfall over 24 hours (RX1), over 5 days (RX5), the 95th and 99th percentiles (R95 and R99), the Rainfall Anomaly Index (RAI) and trend analyses using the Mann-Kendall method, as well as loss and damage data were then calculated. The results did not indicate a trend towards an increase in precipitation extremes, although they did confirm the February 2022 event as an extreme event, which stood out as the largest within the historical series analysed.